Strategy-based listening and pragmatic comprehension - Corsetti, Cristiane Ruzicki (Brazilian English Language Teaching Journal, 2014)
This article addresses the role of strategy-based listening as an alternative methodological approach to develop pragmatic comprehension in L2 contexts. Pragmatic comprehension refers to the understanding of speech acts and conversational implicatures. Listening comprehension comprises both bottom-up and top-down processes. Strategy-based listening encompasses the activation of pragmatic knowledge through pre-listening activities and the development of specific listening micro-skills. An empirical project which included a classroom project carried out with a group of eight learners preparing for the IELTS examination in 2009 corroborated the following assumptions: in order to achieve listening proficiency, learners need practice in making inferences as semantic and pragmatic inferences are embedded in verbal communication; semantic and pragmatic aspects affecting the meaning of utterances can be highlighted via comprehension activities focusing on specific listening subskills. The results of the classroom project suggested that strategy-based listening is potentially capable of directly enhancing pragmatic comprehension but were inconclusive with regards to pragmatic production